Hubungan Pengetahuan , Sikap, Peran, Ibu dengan Kesiapan Anak Menghadapi Menarche di SD Negeri Semeru 06 Kota Bogor - Meti Kusmiati; Fitria Lestari; Nurul Azmi Fauziah; Chesa Alyaina; Endang Sariu; Nazila Aliya Zahraa; Selvi Anggraeni (JURNAL RISET RUMPUN ILMU KESEHATAN, 2025)
Adolescents are the age group from 10 to 19 years who are in the transition period from children to adults. During this period, various changes occurred, both physical, psychological and social. The aim is to analyze the relationship between knowledge of maternal attitudes and roles and girls' readiness to face menarche. The formula method used is the Chi Square Test formula and Spearman Rank Correlation with the SPSS version of the computer program. The results of the research show that children who are not ready are more likely to be found in the group with a supportive mother's role at 32.6%, compared to the group whose mother's role is not supportive at 6.7%. Based on the results of the Chi square statistical test, the result is a p value of 0.049 = meaning <0.05, so Ha is accepted, which means there is a relationship between the role of the mother and the readiness of female students at SD Negeri Semeru 06 in 2024. Furthermore, the or value in this research was found to be 0.1 with So it can be concluded that a supportive maternal role has a 0.1 times chance of being well prepared compared to a non-supportive maternal role. Conclusions Based on research at SDN Semeru 06 Bogor City (2024) shows that the majority of respondents had a poor understanding of menstruation, but their understanding increased after counseling.Abstract and Keywords must be written in